Task type and incidental L2 vocabulary learning: Repetition versus task involvement load. Issue 2 (30th June 2016) - Ansarin, Ali Akbar; Bayazidi, Aso
Abstract: This study investigated the effect of task type on incidental L2 vocabulary learning. The different tasks investigated in this study differed in terms of repetition of encounters and task involvement load. In a within-subjects design, 72 Iranian learners of English practised 18 target words in three exercise conditions: three multiple-choice exercises, three fill-in-the-blank exercises, and one sentence-making exercise. An unannounced receptive vocabulary recall post-test was used to measure the participants' retention of the meaning of the target words. The results revealed that exercise condition had a significant effect on the mean scores for the three conditions, with words practised under the three multiple-choice and the three fill-in-the-blank exercises conditions being recalled significantly better than those practised under the one sentence-making condition. However, there was no significant difference between the three multiple-choice and the three fill-in-the-blank conditions. The results suggest that incidental vocabulary learning is more affected by repetition of encounters than by elaboration of meaning.